Upaya Meningkatkan Hasil Belajar Matematika melalui Model Pembelajaran Kooperatif Jigzaw di kelas IX-A SMP Negeri 3 Kesugihan - Suprapti, Suprapti (Sahabat Publikasi, 2024)
The purpose of this study is to improve the learning outcomes of students in mathematics subjects on the material of building curved side space through the Jigzaw cooperative learning model in grade IX SMP Negeri 3 Kesugihan Cilacap Regency. One of the efforts to improve learning outcomes is through the learning process using the Jigzaw cooperative learning model. The method used is the Kemmis and Mc Taggart model Classroom Action Research methods which consist of two cycles. This research was conducted from September 2020 to October 2020 in class IX-A SMP Negeri 3 Kesugihn Kab. Cilacap. The indicators of learning outcomes achieved in siculus I are the completeness of student learning reaching 71.8% with an average value of 71.8 and in cycle II the completeness of student learning reaches 100% with an average value of 96.61. This is supported by the average value of student activity which always increases in each cycle, namely in cycle I it reaches 71.8% and cycle II reaches 100%. Thus, it can be concluded that Jigzaw's cooperative learning model can improve student learning outcomes on the material to build curved side spaces.